Pengelolaan Harta Pusaka Tinggi Dalam Masyarakat Adat Minangkabau (Studi di Kecamatan Batipuh Kabupaten Tanah Datar) - Rahmat, Indra (Laboratorium Program Studi Pendidikan Sejarah Sekolah Tinggi Keguruan dan Ilmu Pendidikan, 2019)
This study was to determine the management of high inheritance in Minangkabau indigenous society. It was a socio-legal research or non doctrinal research. It observed the empirical data descriptively. It analyzed law effectiveness by comparing between das sollen and das sein. Data were collected by implementing library research method using documentary study technique in written materials. Meanwhile, a field research used direct communication technique using interview guideline. Sampling method was a purposive sampling. Drawing conclusions was conducted by implementing inductive method, and data analyzing was conducted qualitatively. The research finds out that the management of high inheritance in Minangkabau indigenous society can occur in the form of land inheritance and others. The management of land inheritance, which is based on ganggam bauntuak, can be managed by ganggam bauntuak holder society and other people based on the agreement. The management of non-land inheritance is an effort to preserve the inheritance due to the transition from land inheritance to other inheritance such as gold.